Experimental drugs for the inhibition of preterm labor. (3rd May 2020) - Triggs, Tegan; Kumar, Sailesh; Mitchell, Murray
ABSTRACT: Introduction: Preterm birth is the leading cause of neonatal morbidity and mortality globally and poses a substantial economic burden. Consequently, there is a need for the identification of therapeutic targets and novel experimental drugs for the inhibition of preterm labor to improve neonatal outcomes. Areas covered: The authors review the pathophysiology of labor and the inflammatory pathways underpinning it. The interruption of these pathways forms the basis of therapeutic targets to inhibit preterm labor. Current drugs available for the treatment of preterm labor are reviewed, followed by experimental drugs including toll-like receptor 4 (TLR-4) antagonists, cytokine suppressive anti-inflammatory drugs (CSAIDs), N-acetyl cysteine (NAC), Sulfasalazine (SSZ), tumor necrosis factor-alpha (TNF-α) antagonists, interleukin-1 receptor (IL-1) inhibitors, omega-3 polyunsaturated fatty acids and lipid metabolites, and the polyphenols. Expert opinion: A number of new therapeutic strategies for the prevention of preterm labor are being investigated. These have the potential to improve neurodevelopmental outcomes and survival in babies born preterm, reducing the economic and healthcare costs of caring for the complex needs of these children in the immediate and long term. It is likely that over the next decade there will be a new treatment option that targets the pathological inflammatory processes involved in preterm labor.